Ans y antes: de la anterioridad a la refutación en catalán y en español. - Arguedas, Maria Estellés; Cuenca, Maria Josep (Zeitschrift für Katalanistik, 2017)
The present paper compares the uses of Cat. ans and Sp. antes as a single marker and as a component of parenthetical connectives. They share the same Latin origin, the spatial-temporal adverb ANTE ('before, prior to'), and have developed to a different extent temporal, comparative and contrastive uses. Although in earlier stages ans and antes had refutative values on their own, nowadays these meanings are found mainly in parenthetical connectives containing the adverb ans / antes, namely ans bé / ans al contrari in Catalan and antes bien / antes al contrario in Spanish. In spite of their apparent similarity and verbatim correspondence in both Romance languages analyzed, a synchronic corpus analysis reveals differences in the frequency and distribution of these markers, both intra- and cross-linguistically. Regarding frequency, ans al contrari is more common in Catalan, whereas antes bien appears more often in Spanish. In terms of distribution, distinct positional preferences are found in each language, as well as specific syntactic-discursive combinations.